2021
DOI: 10.3390/microorganisms9081742
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gut Dysbiosis Alters Offspring Microbiota and Social Interactions

Abstract: Increasing application of antibiotics changes the gut microbiota composition, leading to dysbiosis of the gut microbiota. Although growing evidence suggests the potential role of gut dysbiosis as the cause of neurodevelopmental disorders and behavioral defects, a broad gap of knowledge remains to be narrowed to better understand the exact mechanisms by which maternal gut dysbiosis alters microbiota development and social interactions of offspring. Here, we showed that maternal gut dysbiosis during gestation is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
(68 reference statements)
0
6
0
1
Order By: Relevance
“…Similarly, perturbations of the maternal gut microbiota (termed dysbiosis) are also a risk factor for adverse pregnancy outcomes, such as miscarriage and intrauterine growth restriction; and recent evidence highlights potential long-term effects of maternal dysbiosis on offspring metabolic and neurological health, resulting in obesity and mental health disorders [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, perturbations of the maternal gut microbiota (termed dysbiosis) are also a risk factor for adverse pregnancy outcomes, such as miscarriage and intrauterine growth restriction; and recent evidence highlights potential long-term effects of maternal dysbiosis on offspring metabolic and neurological health, resulting in obesity and mental health disorders [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics were administered to mice in the adolescent phase of life in 23 articles (30 populations; Table 4 ). None and only one of the study populations displayed changes in sociability and social novelty, respectively after antibiotic administration regardless of sex, strain, or duration between treatments and behavioral observations ( Table 4 ; Gacias et al, 2016 ; Guida et al, 2018 ; Lach et al, 2020 ; Zhang Z. et al, 2021 ). Similarly, recognition memory decreased in only one of the study populations tested ( Guida et al, 2018 ; Lach et al, 2020 ; Saunders et al, 2020 ; Arslanova et al, 2021 ; Luo et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies also reported behavioral changes in offspring born to mothers given antibiotic cocktails but the results were inconsistent and cannot be generalized. A decrease in social novelty preference without change in sociability was observed in 98 days-old mice of either sex born to mothers given neomycin and vancomycin ( Zhang Z. et al, 2021 ). Tochitani et al (2016) reported an increase in anxiety without changes in sociability in 28 day-old mice of either sex born to mothers administered neomycin, bacitracin, and pimaricin.…”
Section: Resultsmentioning
confidence: 99%
“…The production of many of such metabolites, such as short-chain fatty acids, tryptophan metabolites, and bile acids, are themselves dependent on the presence, abundance, and function of the gut microbiota 39 . High throughput, next-generation metabolomics, a technique to measure the thousands of such metabolites, can now detect these molecules in a sample and can be an excellent proxy for how one's life history has influenced one's response to stress 40–47 . For example, in the elite survivor study mentioned previously, investigators demonstrated that microbiome-derived indoles became enriched in the plasma, resulting in their known binding to the aryl-hydrocarbon receptor on macrophages with subsequent activation of a recovery-directed immune response.…”
Section: Can a Comprehensive Analysis Of The Gut Microbiome Reflect T...mentioning
confidence: 99%
“…39 High throughput, next-generation metabolomics, a technique to measure the thousands of such metabolites, can now detect these molecules in a sample and can be an excellent proxy for how one's life history has influenced one's response to stress. [40][41][42][43][44][45][46][47] For example, in the elite survivor study mentioned previously, investigators demonstrated that microbiome-derived indoles became enriched in the plasma, resulting in their known binding to the arylhydrocarbon receptor on macrophages with subsequent activation of a recovery-directed immune response. In summary, converging lines of evidence suggest that a more comprehensive analysis of how the patient's life history and social determinants of health is reflected within the compositional and functional output (i.e., metabolites) of the gut microbiome has the potential to advance our understanding of the "within-group" variability in outcome that occurs from a given disease state and its treatment.…”
mentioning
confidence: 99%